Men in Manual Occupations Changing Lives in Times of Change - Chelsom Vogt, Kristoffer (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2017)
A shortage of skilled workers is currently emerging in many countries. Yet public discourse and much research literature convey the impression that manual labor is somehow outmoded, requiring competencies that are no longer necessary in today's «post-industrial, information-based society». The question of how to achieve the right balance between different types of work in a society is one that transcends national borders.